A Privilege not a Choice Transnational Support Networks of Asylum Seekers and Expatriates - Hoór, Dorottya (2021)
The article explores how different factors shape migrants’ transnational social fields and support networks through a comparative study of two different groups of migrants—asylum seekers and expatriates—in Budapest, Hungary. To do so, the study employs a parallel mixed‐methods social network design by combining personal network data with qualitative data based on interviews and ethnographic fieldwork with thirty‐three migrants in the aftermath of the 2015 refugee crisis. The article presents three key findings: First, it finds that asylum seekers’ and expatriates’ networks differ on several key characteristics, as asylum seekers’ close personal networks are less efficient, smaller in size, and show a remarkable lack of friendship and transnational support ties. Second, it also finds that asylum seekers have limited access to social support and, especially so, to financial and emotional support. Lastly, using multi‐level models, the article also demonstrates how migrants’ legal status and the transnationality of their support ties affect their access to financial support, as well as how their gender and legal status shape their access to emotional support. These findings illustrate how migrants’ individual opportunity structures affect their transnational practices alongside their access to social support, while also highlighting the importance of several individual and contextual factors which contribute to the diverse integration processes of migrants.
Keywords: Asylum Seekers; Expatriates; Migration; Personal networks; Social Networks; Social Support; Transnationalism